ANALYZE QUEUE PERFORMANCE USING ARENA 16.0 SOFTWARE (Z Cinema Case Study) - Fredlina Margaret; Sofwan Ali Fakhrudin; Ariska Dithya Pratiwi; Fergyanto E. Gunawan (JARES (Journal of Academic Research and Sciences), 2023)
Queues are often found in everyday life, such as waiting for cinema counters, check-in queues at airports and self-service cashier queues. Service facilities for a long time cause queues because they cannot meet the needs or capacity, so facility users have to wait. As in the example of the case of Cinema Z in Solo City has a maximum queue time of 13.6 minutes with a maximum number of queues of 11 people until served. This can cause customers to wait long enough to get movie tickets. This problem can be overcome by the need to manage the counter operator so that it can regulate when to open a new counter so that there is no queue. This research discusses the problem of queuing models at Cinema Z in Solo, Central Java Province. From the results of the analysis that can be known the performance values of the queuing system such as waiting time, number in, number out, dan number waiting.